Assignment of the NAD-dependent deacetylase sirtuin 5 gene (SIRT5) to human chromosome band 6p23 by in situ hybridization - Mahlknecht, Ulrich Rudolph; Ho, Anthony Dick; Letzel, Stephan; Völter-Mahlknecht, Susanne Friederike (Cytogenetic and genome research, 2006)
Sirtuin 5 (SIRT5) is a nicotinamide adenine dinucleotide (NAD)-dependent deacetylase and belongs to the Silent information regulator 2 (Sir2) family of sirtuin histone deacetylases (HDACs), which play a central role in epigenetic gene silencing, DNA repair and recombination, cell-cycle, microtubule organization, and in the regulation of aging. We have isolated and characterized the human SIRT5 genomic sequence, which spans a region of 28,182 bp and which has one single genomic locus. Human SIRT5 consists of eight exons and is found in two isoforms, which encode a 310 aa and a 299 aa protein, respectively. Human SIRT5 is most predominantly expressed in heart muscle cells and in lymphoblasts. Fluorescence in situ hybridization analysis localized the human SIRT5 gene to chromosome 6p23.